Immunity in Experimental Syphilis IV. Serological Reactivity of Antigens Extracted from γ-Irradiated Treponema pallidum and Treponema reiteri - Miller, James N. (1966)
Miller, James N. (University of California School of Medicine, Los Angeles), J. H. De Bruijn, and J. H. Bekker. Immunity in experimental syphilis. IV. Serological reactivity of antigens extracted from γ-irradiated Treponema pallidum and Treponema reiteri. J. Bacteriol. 91:583–587. 1966.—Ultrasonic lysate preparations extracted from virulent Treponema pallidum, Nichols strain, suspensions exposed to 652,800 R of γ-irradiation exhibited a loss in the serological reactivity of their heat-labile antigens; the heat-stable components of both the lysate and residue antigens were unaffected. The activity of heat-stable, cardiolipin T. pallidum complement-fixing antigen obtained from similarly irradiated organisms was also unaltered. γ-Irradiation of the cultivable Treponema reiteri with dosages as high as 6,500,000 R failed to alter serologically either the heat-labile or heat-stable component of its lipopolysaccharide-protein (Reiter protein) antigen. The reactivity of the lipopolysaccharide portion of the Reiter protein complex with an antiserum to T. pallidum Nichols indicates previously unsuspected antigenic differences between the rabbit-adapted Nichols strain of the organism and so-called “wild” human strains of T. pallidum in which this antigen is generally absent.